2021
DOI: 10.1136/bmjopen-2020-043245
|View full text |Cite
|
Sign up to set email alerts
|

‘Because Everybody is so Different’: a qualitative analysis of the lived experiences and information needs of rectal cancer survivors

Abstract: ObjectiveTo (1) characterise (A) the lived experiences and (B) information needs of patients with rectal cancer; and (2) compare to the perceived lived experiences and information needs of colorectal surgeons.DesignWe conducted 1-hour semistructured qualitative interviews, dual independent transcript coding and thematic analysis.Setting/participantsInterviews included rectal cancer survivors (stages I–III), some accompanied by caregivers, at Dartmouth-Hitchcock Medical Center and experienced colorectal surgeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…The survey was developed after prior qualitative work identified that patients diagnosed with rectal cancer who had undergone surgical treatment felt they could have used more information/support regarding ostomy care. The motivation for the study was based on our previous qualitative work on the lived experience of rectal cancer survivors in which an extensive qualitative analysis was conducted [14]. From this work, we identified areas of improvement, including differences in perception and knowledge of physicians about ostomies, the value of wound ostomy and continence nurses and the misinformation provided to people with ostomies regarding the clinical care of an ostomy.…”
Section: Patient and Public Involvement And Designmentioning
confidence: 99%
“…The survey was developed after prior qualitative work identified that patients diagnosed with rectal cancer who had undergone surgical treatment felt they could have used more information/support regarding ostomy care. The motivation for the study was based on our previous qualitative work on the lived experience of rectal cancer survivors in which an extensive qualitative analysis was conducted [14]. From this work, we identified areas of improvement, including differences in perception and knowledge of physicians about ostomies, the value of wound ostomy and continence nurses and the misinformation provided to people with ostomies regarding the clinical care of an ostomy.…”
Section: Patient and Public Involvement And Designmentioning
confidence: 99%
“…75 Qualitative work supports that rectal cancer survivors experience major-but varied-impacts on their lives informed by medical experiences, lifestyles, and attitudes, regardless of permanent ostomy or reconstruction after TME. 78 Other studies have found lower scores with permanent ostomies in some domains. [79][80][81][82][83][84][85][86][87][88][89][90] Lower body image scores in patients with permanent ostomies is the most common domain affected.…”
Section: Sphincter Preservation As An Outcome Measurementioning
confidence: 93%
“…76 Moreover, those with permanent ostomies can endure parastomal hernias, prolapse, and pouching dysfunction that rivals the incontinence and pelvic floor dysfunction with reconstruction. 78 Quality of life may be lower in younger patients than older ones irrespective of permanent ostomy or reconstruction. 75 Qualitative work supports that rectal cancer survivors experience major-but varied-impacts on their lives informed by medical experiences, lifestyles, and attitudes, regardless of permanent ostomy or reconstruction after TME.…”
Section: Sphincter Preservation As An Outcome Measurementioning
confidence: 99%
“…There were no patients involved in the concept, design, analysis or drafting of the study results, nor was any patient involved in the distribution of the survey. The authors write that they used a prior study to advise on the lived experience for the current work [23]. However, there were no common themes or questions, and the only applicable result for the current work was that surgeons did not report knowledge of the full range of patient experiences and reported limited counselling in key areas important to patients [23].…”
mentioning
confidence: 99%
“…The authors write that they used a prior study to advise on the lived experience for the current work [23]. However, there were no common themes or questions, and the only applicable result for the current work was that surgeons did not report knowledge of the full range of patient experiences and reported limited counselling in key areas important to patients [23]. This gap between patients and surgeons is even more reason to include patients and those with the lived experience in the research.…”
mentioning
confidence: 99%